Influence of determinant factors on Jambi medical students’ awareness of seeking oral health information on social media: a cross-sectional study - Wijayanti, Zilzikridini; Hardiningsih, Denok Tri; Buana Perkasa, Tengku Arief; Amatullah, Afifah (Universitas Padjadjaran, 2026)
Introduction: Social media has become an effective and easily accessible means of acquiring oral health literacy in the digital era 5.0. Therefore, this study aimed to analyze the influence of determinant factors affecting Jambi medical students’ awareness of seeking oral health information on social media. Method: This analytical cross-sectional study analyzed the association between determinant factors affecting Jambi medical students' awareness of seeking oral health literacy on social media. A total of 292 participants were selected using purposive sampling. The instrument was divided into five sections. The second and fifth sections were measured using a Likert scale and analyzed using multiple linear regression. Results: The higher the frequency of seeking oral and dental health information through social media, the greater the awareness of seeking oral health information on social media (regression coefficient=0.581; t=10.248; p<0.001). A higher level of trust was also associated with greater awareness of seeking oral and dental health information on social media (regression coefficient=0.431; t=10.314; p<0.001). Respondents with good oral and dental health maintenance behavior were more likely to be positively influenced by oral and dental health information and content on social media (regression coefficient=0.344; t=8.255; p<0.001). Conclusion: Social media plays an important role in shaping individual awareness, particularly when users have high levels of trust and actively seek relevant oral and dental health information. Trust was identified as a key determinant in influencing awareness of oral health literacy on social media.